2012
DOI: 10.1039/c2ra21714g
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanocomposite films of polyvinyl alcohol and ZnO as interactive gas barrier layers for electronics device passivation

Abstract: The development of low cost, easy processable, barrier encapsulant materials is of critical importance for the rapid commercialization of organic/electronic devices. In this study, flexible and thermally stable composites were prepared by simple solution processing using polyvinyl alcohol as the base polymer matrix and reactive zinc oxide nanoparticles as the dispersed phase. These materials were characterized for their applications as barrier materials for moisture and oxygen sensitive organic devices. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The use of multilayered composite film structure of alternating polymer and metal oxide had been reported in the literature but these systems are not cost effective and not flexible. The presence of nanofillers in the polymer matrix results in increased mechanical stability, chemical resistance, and high moisture barrier resistance, which could be potentially used for device encapsulation applications .…”
Section: Introductionmentioning
confidence: 99%
“…The use of multilayered composite film structure of alternating polymer and metal oxide had been reported in the literature but these systems are not cost effective and not flexible. The presence of nanofillers in the polymer matrix results in increased mechanical stability, chemical resistance, and high moisture barrier resistance, which could be potentially used for device encapsulation applications .…”
Section: Introductionmentioning
confidence: 99%
“…The lifetimes of the devices under these accelerated conditions are equivalent to $1000 times the lifetimes at 25 C and 45% RH. 28,29 Representative I-V curves for the encapsulated (S0, SSC3, MSC3, and OTE3) and unencapsulated devices are given in Figure S6. 25 From device (I-V) characteristics, it was observed that the device current decreases with increasing time of exposure to accelerate weathering conditions.…”
mentioning
confidence: 99%
“…PVA/ZnO-based composite was optimized for barrier property from calcium degradation test and organic device encapsulation results. Encapsulation with this optimized composite material improved the device lifetime by four times compared to the lifetime of non-encapsulated organic device [72].…”
Section: Materials For Encapsulationmentioning
confidence: 91%